Adaptive Governance in Achieving Food Self-Sufficiency and Family Resilience in Baubau City - Inzana, Nur; Asiri, La; Sari, Mawang (Universitas Pancasakti, 2025)
The urgency of this research stems from the high prevalence of undernourishment (PoU), or the prevalence of food insufficiency at 10.84% in 2023, and the Food Security Index (IKP), which only reached 80.49 in 2024, indicating limited access to sufficient, nutritious, and sustainable food in Baubau City. This condition can impact the overall welfare of families, so effective strategies are needed to improve food security in the area. This study aims to explore the role of adaptive governance in increasing the effectiveness of food self-sufficiency policies and strengthening family resilience in Baubau City. This research method employed a qualitative approach, utilizing data collection methods that included interviews, observation, documentation, and Focus Group Discussions (FGDs). Key informants included the Baubau City Agriculture and Food Security Office (Dipertan), the Baubau City Health Office, local farmer groups, and community self-help communities. Data were analyzed using NVivo 12 Plus. The findings of this study confirm that food security in Baubau City remains vulnerable due to a combination of structural, social, and economic factors. However, the implementation of adaptive governance offers a strategic opportunity to strengthen the local food system. With policy flexibility, cross-sector collaboration, digital technology integration, and a focus on strengthening nutritional literacy and family empowerment, Baubau can reduce its dependence on external supplies while building household food resilience. This demonstrates that family resilience and food self-sufficiency in Baubau can only be achieved through an adaptive approach that integrates the roles of government, communities, and the private sector in building a more inclusive, resilient, and sustainable food system.